Sudden Death Due to Spontaneous Rupture of the Urinary Bladder following Acute Alcohol Inebriation- A Case report and Review of Literature - Sah, Bikash; Jha, Shivendra; Pokharel, Dikshant (International Journal of Global Health, 2020)
Spontaneous rupture of the urinary bladder (SRUB) is a rare clinical condition. Prompt diagnosis is often difficult both clinically and radiologically and necessitates a high index of suspicion as the patients present with non-specific abdominal pain and may not offer a clear history. The depressant effect of alcohol further complicates the diagnosis. We report a case of a young male who was unable to seek medical support and was found dead within 12 hours of the onset of abdominal discomfort following acute alcohol intoxication. At autopsy, rupture of the urinary bladder with blood and blood clots was found in the pelvic cavity with no any corresponding external injury. Spontaneous rupture of the urinary bladder is a rare cause of death in acute alcohol intoxication. In order to further understand this rare condition, the review of related literature has been done.
Keywords: Death; Diuretics; Rupture; Urinary Bladder